A Short Journey from Quarks to the Universe - Economou, Eleftherios N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book takes the reader for a short journey over the structures of matter showing that their main properties can be obtained even at a quantitative level with a minimum background knowledge. The latter, besides some high school physics and mathematics, consists of the three cornerstones of science presented in chapters 1 to 3, namely the atomic idea, the wave-particle duality, and the minimization of energy as the condition for equilibrium. Dimensional analysis employing the universal constants and combined with (3z(Ba little imagination and thinking(3y(B, to quote Feynman, allows an amazing short-cut derivation of several quantitative results concerning the structures of matter. This book is expected to be of interest to physics, engineering, and other science students and to researchers in physics, material science, chemistry, and engineering who may find stimulating the alternative derivation of several real world results, which sometimes seem to pop out the magician$1 (Bs hat.s
Preface -- Introduction: The World according to Physics Levels of the structure of mater -- PART 1: Three key-ideas and a short-cut -- The atomic idea -- The wave-particle duality -- Equilibrium and minimization of total energy -- Dimensional analysis: A short-cut to physics relations -- PART 2: This World, this small World, the great -- From quark and gluons to hadrons -- From protons and neutrons to nuclei -- From nuclei and electrons to atoms -- From atoms to molecules -- From atoms and molecules to solids and liquids -- Planets -- Stars, dead or alive -- Cosmology -- Revisiting photons.
Keywords: Physics; Geography; Physics; Atomic, Molecular, Optical and Plasma Physics; Astrophysics and Astroparticles; Classical and Quantum Gravitation, Relativity Theory; Optics and Electrodynamics; Applied Earth Sciences